Economic Value Added (EVA) Disclosure Practices of Sri Lankan Listed Companies - Thilakerathne, P.M.C. (Journal of Finance and Accounting, 2015)
Transparency, disclosures and information sharing with stakeholders, command a considerable degree of value to the accompanying financial statements of any corporate or business enterprise. Investors and stakeholders are increasingly looking at the performance of companies which they have invested their hard earned funds. To meet such expectations, good governed companies do adopt practices which add to enhance the value of financial statements and value to its readers. The ideas of free cash flow and the evaluation of business on a cash basis developed by Modiglaini and Miller (1961) were extended into the concept of the Economic Value Added (EVA) (Stewart and Stern 1971). The traditional financial performance measures have not presented the real shareholder value of an enterprise. Thus, the EVA is one of main evaluation criteria of companies’ commitment with shareholder value maximization. In this context, this research investigated the EVA disclosures in the annual reports of Sri Lankan listed companies. Analyzing annual reports of Sri Lankan largest 85 listed companies over a period of 5 years from 2009 to 2013, the results indicated that 15 numbers of listed companies, as a percentage of 17.65 of the sample disclosed the EVA statement in their annual reports. The study further explored the industry composition, residential status, medium of disclosure, areas of EVA application and extent of EVA related computation prepared and disclosed by EVA reporting companies. Univariate analysis was used to identify the extent of EVA disclosures of listed companies in Sri Lanka and it was found that, existence of significant inconsistencies and irregularities in measurement of EVA and its major components of EVA reporting listed companies. The second part of the study explored that the corporate attributes such as back ground information and financial performance indicators of companies are influenced to the choice of EVA disclosure. Therefore, research performed a comparison of differences between EVA reporting and EVA non reporting listed companies on the basis of their background indicators and financial performance measures. Research employed the two independent sample t-tests to identify the factors influencing to EVA usage and disclosure choice of Sri Lankan listed companies in terms of company size, profitability, leverage etc. Research finds that the EVA usage and EVA disclosure choice of Sri Lankan companies are influenced by the company size, leverage and earnings potential. Further, the study recommends the importance of implementing EVA disclosures as a mandatory requirement for Sri Lankan listed companies.
Keywords: Economic Value Added; EVA Disclosures; Colombo Stock Exchange; EVA Disclosure Mediums; Financial Performance of Listed Companies